Homocysteine as a biomarker of physical activity and exercise tolerance in adolescent children - Nataliia Shliakhova; Larysa Rak; Vitalii Muzhanovskiy (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose: To determine the homocysteine content in children and adolescents with different levels of physical activity, to establish the relationship between homocysteine content, indicators of physical development, level of physical activity and tolerance to physical activity in adolescence.